CpG Frequency in the 5′ Third of the env Gene Determines Sensitivity of Primary HIV-1 Strains to the Zinc-Finger Antiviral Protein - Dorota Kmiec (American Society for Microbiology, 2020)
ABSTRACT CpG dinucleotide suppression has been reported to allow HIV-1 to evade inhibition by the zinc-finger antiviral protein (ZAP). Here, we show that primate lentiviruses display marked differences in CpG frequencies across their genome, ranging from 0.44% in simian immunodeficiency virus SIVwrc from Western red colobus to 2.3% in SIVmon infecting mona monkeys. Moreover, functional analyses of a large panel of human and simian immunodeficiency viruses revealed that the magnitude of CpG suppression does not correlate with their susceptibility to ZAP. However, we found that the number of CpG dinucleotides within a region of ∼700 bases at the 5′ end of the env gene determines ZAP sensitivity of primary HIV-1 strains but not of HIV-2. Increased numbers of CpGs in this region were associated with reduced env mRNA expression and viral protein production. ZAP sensitivity profiles of chimeric simian-human immunodeficiency viruses (SHIVs) expressing different HIV-1 env genes were highly similar to those of the corresponding HIV-1 strains. The frequency of CpGs in the identified env region correlated with differences in clinical progression rates. Thus, the CpG frequency in a specific part of env, rather than the overall genomic CpG content, governs the susceptibility of HIV-1 to ZAP and might affect viral pathogenicity in vivo. IMPORTANCE Evasion of the zinc-finger antiviral protein (ZAP) may drive CpG dinucleotide suppression in HIV-1 and many other viral pathogens but the viral determinants of ZAP sensitivity are poorly defined. Here, we examined CpG suppression and ZAP sensitivity in a large number of primate lentiviruses and demonstrate that their genomic frequency of CpGs varies substantially and does not correlate with ZAP sensitivity. We further show that the number of CpG residues in a defined region at the 5′ end of the env gene together with structural features plays a key role in HIV-1 susceptibility to ZAP and correlates with differences in clinical progression rates in HIV-1-infected individuals. Our identification of a specific part of env as a major determinant of HIV-1 susceptibility to ZAP restriction provides a basis for future studies of the underlying inhibitory mechanisms and their potential relevance in the pathogenesis of AIDS.